Factors constraining extension workers effectiveness in improving horticultural production: a case study from West Timor, Indonesia - Leta, R.; Murray-Prior, Roy; Rola-Rubzen, Maria Fay (International Society of Horticultural Science, 2005)
The Indonesian government and the government of Nusa Tenggara Timur recognise that horticulture is economically important and is expected to become the leading agribusiness sector to overcome poverty for farmers. Hence, in the last 20 years, the government of Nusa Tenggara Timur through various agribusiness projects has encouraged the planting of more than 18,490 hectares of vegetables and 82,010 hectares of fruit. The major producing areas of both are in the Kupang district and in the Timor Tengah Selatan. However, productivity is low. If production can be increased, on-farm income may also increase, but this is dependent upon Agricultural Extension Workers performing their roles more effectively. This study investigates the constraints that impede the ability of Agricultural Extension Workers to effectively perform their roles. The results suggest that while Agricultural Extension Workers are not performing their roles effectively there are a number of reasons for this, many of them beyond the control of Agricultural Extension Workers. While the Nusa Tenggara Timur province is supposedly following the Training and Visits model Agricultural Extension Workers receive very little training. Other major constraints identified include the constant restructuring of the Agricultural Department, poor remuneration, oppressive authority, inadequate infrastructure, unclear job direction, geographical condition, and bureaucracy. Unless these constraints are addressed, the system will remain unable to deliver the information and skills necessary for farmers to overcome poverty.